Prevalência de trauma cranioencefálico em vítimas de acidente de trânsito com motocicleta atendidas em Hospital de Emergência e Trauma - Ferreira, Fábio Henrique Costa (2016)
Objective: To identify the prevalence of traumatic brain injury (TBI) in traffic accident victims with motorcycle assisted in a hospital of emergency and trauma. Methods: Cross- sectional study with a probabilistic sample composed by 309 medical records of patients victims of traffic accidents involving motorcycles during the period from January to December 2014, attended in Hospital Dom Luiz Gonzaga Fernandes in Campina Grande - PB. The research instrument consisted of a form containing the following variables: gender, age, day and hospitalization time, presence and type of bone fracture, presence of TCE, helmet, Glasgow coma scale, Marshall classification and the occurrence of death. It was realized a descriptive analysis of data using SPSS software 18. For bivariate analyzes were used the chi - square test and Fisher's exact, considering the value of statistical significance (p <0.05). Results: The prevalence of traumatic brain injury in traffic accident victims with motorcycle was 24.3%. There was a predominance of male victims (79.6%) and the age group of 21-30 years. It was found that the highest frequency of hospital admissions were recorded on Sundays (31.1%) and Saturdays (15.9%), predominantly night shifts (36.9%) and afternoon (28.8%).It was found statistically significant differences in the associations between TCE and helmet use (p = 0.008) and TCE and death (p = 0.001). Conclusion: It was observed a high prevalence of TBI in motorcycles traffic accident victims. The non-use of the helmet was associated with a higher frequency of TBI and the victims with TBI had higher risk to progress to death.